Shear Bond Strength of Metal Brackets Recycling with Aluminum Oxide - Borja de Melo, Téssia Richelly Nóbrega; Youssef, Michel Nicolau (The Journal of Dentists, 2020)
Objective: to evaluate the shear bond strength of metal brackets subjected to recycling with aluminum oxide. Methods: 20 premolars were used, divided into two groups (n = 10) according to the brackets used (G1: Morelli® Light and G2: Morelli® Max). The teeth were autoclaved, included in ¾-inch PVC tubes, perpendicular to the ground. The brackets were fixed on the dental crowns with the TransbondTM XT kit (3M Unitek). The specimens were subjected to thermal cycling. The shear test was performed on the Instron® 5582 testing machine, at a speed of 0.5mm / min. The brackets were recycling with aluminum oxide 24 hours after the test. A new shear was performed, similar to the first. The buccal faces of the teeth were qualified through the IRA in both tests. The data were submitted to statistical analysis using the Kruskal-Wallis, ANOVA and Tukey tests (p <0.05). Results: in the first shear, the bond strength values of Morelli® Max brackets (35,00MPa) were statistically higher than those of Morelli®Light (23,86MPa). In the second, the resistances were statistically similar (Morelli®Max: 37,19 MPa and Morelli®Light: 45,18 MPa). The Morelli® Light bracket was influenced by the recycling of aluminum oxide, with a significant increase in resistance from the first to the second test. There was no significance for the values of the IRA scores in both trials. Conclusion: recycling with aluminum oxide influenced the shear bond strength of the Morelli®Light bracket, causing an increase in adhesion strength; the Morelli® Max bracket was superior to Morelli® Light before recycling; after recycling, the brackets had similar behaviors.